PENILAIAN ARAH KESTABILAN EKOSISTEM PADA LAHAN REKLAMASI BEKAS TAMBANG BATUBARA DI LOKASI BINUNGAN PT. BERAU COAL KALTIM - , Nasiatul Azizah, Dr. Retno Peni Sancayaningsih, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Re-vegetation for reclamation in ex-coal mining area could ecologically improve and recover the degraded vegetation cover through intensive re-planting and maintenance, and this reclamation activity contributes in reducing CO2 emission through photosynthesis process. Effectively, this is also able to minimize land erosion and land fertility status. The objectives of this research are 1) to analyze plants structure on reclamation area and secondary forests, 2) to estimate plants carbon stock, and 3) to assess ecosystem stability based on soil fertility status. Research location and extrapolation NDVI data are selected from Landsat 8 satellite imagery. Vegetation analysis was used by implementing sampling square method in 30 x 30 m2 plot size with 3 replicates at every forest condition, established in 5 selected areas including no mining activity as a control, 2 years re-vegetation, 3 years re-vegetation, 7 years re-vegetation, and 9 years re-vegetation. Allometric method was used to calculate biomass and estimate the carbon stock. Hence, the effectiveness of re-vegetation implementation could be seen based on its ability in decreasing erosion rate and soil fertility status by soil chemical analysis. The research results showed direction of ecosystem stability have seen similar plants structure in reclamation area though more uniform because monoculture system from fast growing species for instance family Dipterocarpaceae. Meanwhile, the structures of secondary forests were more heterogenic which consist of 80 plant species with completed growthform. Furthermore, regression among vegetation index (NDVI) that had been derived from Landsat 8 satellite imagery with biomass calculation accounted for R2 0,729. The implementation of equation y = 20604 x - 8756 for biomass value resulted 47,84 ton/ha. Afterwards, based on the biomass value, the carbon stock estimation value constituted 22 ton/ha. Carbon sequestration in forest plantation value resulted 6,46 ton/ha/th. Status of nutrient at the > 7 years revegetation in PT. Berau Coal have increased trend closer to secondary forests conditions.